Los Tres Documentos que Hicieron América [The Three Documents that Made America, in Spanish] La Declaración de Independencia, La Constitución de los Estados Unidos, y La Carta de Derechos [The Declaration of Independence, The Constitution, and The Bill of Rights] - Sam Fink (Blackstone Audio, 2012)
Una de las líneas más citadas dentro de la historia de los Estados Unidos es el derecho que todos los hombres tienen a "la vida, la libertad, y la búsqueda de la felicidad". Es en los documentos fundadores de los Estados Unidos de América que este país encuentra su gran espíritu. Escuche estos documentos en su totalidad traducidos al el español: La Declaración de Independencia (1776), La Constitución de Los Estados Unidos de América (1778) y La Declaración de Derechos (1791). Con una Introducción especial por el legendario artista Sam Fink, ésta es una invaluable producción en audio para todo aquel interesado en la historia de este gran país. [English Translation: One of the most quoted lines in the history of the United States is the right that all men have to "life, liberty, and the pursuit of happiness." It is in the founding documents of the United States of America that this country finds its great spirit. Listen to the documents in their entirety in Spanish translation: The Declaration of Independence (1776), The Constitution of the USA (1787), and The Bill of Rights (1791). With a special introduction by an American artistic legend, Sam Fink, this is an invaluable audio to anyone interested in the history of this great land.] Note: This audio-book is in Spanish. A Blackstone Audio production.